Musicality and Musical Sensitivity in Children - Sree , Dr.R. Shanthi (International Journal of Psychosocial Rehabilitation, 2020)
This research paper addresses one of the fascinating questions, Are girls more musical sensitive and emotionally expressive than boys? This study is a part of a larger project on Music and Children. Music is one of the most seminal aspects of human beings and it manifests as unspoken desire and human essence in their expressions of everyday life. It is one of the most aesthetically sophisticated forms of human expression. Music is the essence of nature and it knowingly or unknowingly touches the soul of life from the womb to the tomb. The musical sensitivity and creativity of a child starts from the womb of its mother. The fetus lives to the rhythm of its mother’s heartbeat sound and emotion of its mother’s voice. As it grows, it expresses emotions by responding to songs and sounds through movements. What fascinates us is how do boys and girls express their musical creativity and differ in responding to different musical forms. To understand children’s knowledge about music and musical sensitivity the researcher has randomly selected 120 students (73 female and 47 male children) from the schools of Hyderabad. Administering the appropriate tests the researchers collected the data and the analysis of data revealed significant differences between boys and girls with respect to their musical sensitivity.